PENGARUH PERDAGANGAN ONLINE TERHADAP PERILAKU MASYARAKAT KOTA SEMARANG - Farid Ahmadi; Sunyoto Sunyoto; Anindya Ardiansari (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
The rapid development of information technology including internet bringsgreat impacts in many aspects such as business and sales. Many companies andindividuals use internet as amedia for their sales and business. This will affectsocienty’s behavior in shopping to fulfill theirneeds. This study was aimed to identify the profile of Semarang’s society who are involved in e-commerce andfigure out the effects of e-commerce towards the Semarang’s people behavior.This study is a descriptive research with people in Semarang as thepopulation. Thesamples were determined by using purposive method samplingnamely judgement sampling and quota sampling. The data were gathered throughquestionnaires and interviews. Thus, thedata collected were analyzed descriptive-quantitatively and descriptive-qualitatively.The studyshowed that 70% of Semarang people has done transactionsonline, and were dominated bywomen (58%). They are mostly high schooleducated (60%) under the age of 30 years old. Based on the type of the productsbought, people mostly bought goods (90%) specifically,fashion clothes (63%)and electronics (24%). E-commerce sites that are used to shop online were variedacross various sites (8 sites). Most of all, Shoope (25%) and company websites(21%) were the most two used sites for doing e-commerce. In addition, people inSemarangstill rarely to conduct online transactions with safety factor (42%), Considered as being less secure, as their main reason.